Organic carbon sources, transport, and mineralization in Kermadec Trench sediments - Bai, Shuo; Xu, Hengchao; Liu, Shuangquan; Dong, Liang; Wu, Zijun (Frontiers in Marine Science, 2025)
Hadal trenches are critical hotspots for organic carbon (OC) deposition and diagenesis, yet the mechanisms controlling carbon sequestration, particularly the role of episodic tectonic and volcanic events, remain poorly constrained. This study integrates geochemical analyses of solid sediments and porewater from sediment cores collected at six stations along two transects in the Kermadec Trench to characterize OC sources, transport, and mineralization dynamics within this hadal trench system. Our results reveal a distinct south-to-north sediment transport pattern along the trench axis, leading to an accumulation of marine-derived OC in the south and terrestrial OC in the north. Importantly, earthquake-triggered turbidity currents in the central trench and volcanic eruptions in the north dominate episodic disturbances, exerting primary control over sediment deposition and diagenesis. These downslope currents transport significant OC fluxes from continental slopes to trench axes, enhancing burial rates 20-fold relative to steady-state sedimentation and promoting OC preservation in axial domains. Our findings demonstrate that spatial heterogeneity in hadal carbon cycling is primarily governed by episodic geological events, providing essential insights for accurate quantification of carbon fluxes and their integration into global biogeochemical models.